Effect of Dexmedetomidine on Lactate Clearance in Patients With Septic Shock: A Subanalysis of a Multicenter Randomized Controlled Trial. Issue 2 (August 2018) - Miyamoto, Kyohei; Nakashima, Tsuyoshi; Shima, Nozomu; Kato, Seiya; Ueda, Kentaro; Kawazoe, Yu; Ohta, Yoshinori; Morimoto, Takeshi; Yamamura, Hitoshi
Abstract : ABSTRACT: Lactate clearance is useful to guide initial resuscitation of patients with septic shock. We conducted this study to evaluate whether dexmedetomidine increases lactate clearance in patients with septic shock. This was a randomized controlled trial that involved a post hoc subgroup analysis. Adult patients with septic shock under ventilation were randomized to receive sedation strategy with or without dexmedetomidine (60 in the dexmedetomidine and 51 in the nondexmedetomidine groups). The primary outcome was the lactate clearance at 6 h, defined as the percent decrease in lactate from randomization to 6 h after. The median Acute Physiology and Chronic Health Evaluation II score was 25 (interquartile range 19–31). The median serum lactate value at randomization was lower in the dexmedetomidine group than in the nondexmedetomidine group (4.0 mmol/L vs. 4.8 mmol/L; P  = 0.053). The lactate clearance at 6 h was higher in the dexmedetomidine group, although this was not statistically significant (23.3 ± 29.8 vs. 11.1 ± 54.4, mean difference 12.2, 95% confidence interval (CI), –4.4 to 28.8). After adjusting for the lactate level at randomization, lactate clearance at 6 h was significantly higher in the dexmedetomidine group (adjusted mean difference 18.5, 95% CI, 2.2–34.9). There was no statistically significant difference in the 28-day mortality between the dexmedetomidine and the nondexmedetomidine groups (13 [22%] vs. 18 [35%] patients, P  = 0.11). In conclusion, among mechanically ventilated patients with septic shock, sedation with dexmedetomidine resulted in increased lactate clearance compared with sedation without dexmedetomidine. Abstract : Supplemental Digital Content is available in the text